Protecting his secret son - Scott, Laura, 1961- (Scott, Laura, 1961- Callahan confidential., 2019)
"It's a shock to private investigator Mike Callahan to see Shayla O'Hare again, and with a child in tow--especially with shots flying her way. Protecting the pair must take priority over their tangled past. Is she being targeted for her family's crimes--including possibly killing Mike's father? And what will Mike do when he realizes her son...is actually his son, too?" -- Page [4] cover.